Primary Colorectal Lymphoma: Institutional Experience and Review of a National Database. Issue 10 (October 2019) - Hangge, Patrick T.; Calderon, Esteban; Habermann, Elizabeth B.; Glasgow, Amy E.; Mishra, Nitin
Abstract : BACKGROUND: Primary colorectal lymphoma is rare, representing 0.2% to 0.6% of all colorectal cancers. Because of its low incidence and histologic variety, no treatment guidelines exist. OBJECTIVE: The purpose was to report the experience of primary colorectal lymphoma in an institutional and a national cohort. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted with institutional data composed of 3 tertiary referral centers and national data. PATIENTS: Patients with primary colorectal lymphoma were identified within the Mayo Clinic (1990–2016) and the Surveillance, Epidemiology, and End Results database (1990–2014). MAIN OUTCOME MEASURES: Primary outcomes were overall and 5-year survival. RESULTS: For the institutional cohort (N = 82), 5-year survival was 79.9%. Five-year survival was higher for rectal (88.4%) than for colon tumors (77.2%; p = 0.004). On multivariable analysis, age <50 years was associated with higher overall survival ( p = 0.04). Left-sided colon masses and aggressive histological subtypes were associated with worse survival (0.04 and 0.03). No effect of treatment modality on survival was noted. For the national cohort (N = 2942), 5-year survival was 58.4%. Five-year survival for rectal tumors was 61.0% and 57.8% for colon tumors. On multivariable analysis, factors associated with improved survival were age <70 y, ( p < 0.0001), female sex ( p = 0.005), right-sided masses ( p = 0.02), and diagnoses after 2000 compared with 1990–1999 ( p < 0.0001). Aggressive pathology ( p < 0.0001) and stage III or stage IV presentation compared with stage I ( p = 0.02 and p < 0.0001) were associated with worse survival. LIMITATIONS: The institutional cohort was limited by sample size to describe treatment effect on survival. A major limitation of the national cohort was the ability to describe treatment modalities other than surgery, including chemotherapy and/or no additional treatment. CONCLUSIONS: Poorer survival was noted in elderly patients and in those with aggressive pathology. An overall survival advantage was seen in women in the national cohort. Currently, optimal strategies should follow a patient-centered multidisciplinary approach. See Video Abstract at http://links.lww.com/DCR/A807 . LINFOMA COLORECTAL PRIMARIO: EXPERIENCIA INSTITUCIONAL Y REVISIÓN DE UNA BASE DE DATOS NACIONAL: ANTECEDENTES: El linfoma colorectal primario es poco frecuente, representando del 0.2% al 0.6% de todos los cánceres colorectales. Debido a su baja incidencia y variedad histológica, no existen guías de tratamiento. OBJETIVO: El propósito fue reportar la experiencia en linfoma colorectal primario en una cohorte institucional y una nacional. DISEÑO: Este fue un estudio de cohorte retrospectivo. ESCENARIO: El estudio se realizó con datos institucionales provenientes de 3 centros de referencia terciarios y datos nacionales. PACIENTES: Se identificaron pacientes con linfoma colorectal primario en la base de datos de la Clínica Mayo (1990–2016) y en la base de datos de vigilancia, epidemiología y resultados finales [Surveillance, Epidemiology, and End Results database (1990–2014)]. PRINCIPALES MEDIDAS DE RESULTADO: Los resultados primarios fueron la sobrevida general y a 5 años. RESULTADOS: Para la cohorte institucional (N = 82), la sobrevida a 5 años fue de 79.9%. La sobrevida a cinco años fue mayor en tumores rectales (88.4%) que en los de colon (77.2%; p = 0.004). En el análisis multivariable, la edad <50 años se asoció con una mayor sobrevida general (p = 0, 04). Las masas de colon izquierdo y los subtipos histológicos agresivos se asociaron con una peor sobrevida (0.04 y 0.03). No se observó ningún efecto según la modalidad de tratamiento en la sobrevida. Para la cohorte nacional (N = 2942), la sobrevida a 5 años fue del 58.4%. La sobrevida a cinco años fue de 61.0% para los tumores rectales y 57.8% para los tumores de colon. En el análisis multivariable, los factores asociados con una mayor sobrevida fueron edad <70 años, (p <0.0001), sexo femenino (p = 0.005), masas derechas (p = 0.02) y los casos diagnósticados después del año 2000 comparados con los de 1990–1999 (p <0.0001). Histopatología agresiva (p <0.0001) y presentación en estadio III o estadio IV en comparación con estadio I (p = 0.02 y p <0.0001) se asociaron con una peor sobrevida. LIMITACIONES: La cohorte institucional estuvo limitada por el tamaño de la muestra para describir el efecto del tratamiento en la sobrevida. Una limitación mayor en la cohorte nacional fue la habilidad para describir modalidades de tratamiento distintas a la cirugía, incluyendo quimioterapia y/o ningún tratamiento adicional. CONCLUSIONES: Una menor sobrevida fue documentada en pacientes de edad avanzada y en aquellos con histopatología agresiva. Se observó ventaja en cuanto a sobrevida general en las mujeres de la cohorte nacional. Actualmente, las estrategias óptimas deben de seguir un abordaje multidisciplinario centrado en cada paciente. Vea el abstract en video en http://links.lww.com/DCR/A807 .